An Unusual Case of an Incidentally Detected Angioplasty Wire in the Aorta - Abhinav Karan; Micheal Omar; Gladys Velarde; Srinivasan Sattiraju (Annals of Internal Medicine: Clinical Cases)
A retained angioplasty wire is rarely described, and there are no guidelines as to how it should be managed. Thus the management of this complication remains highly individualized. In the present instance, a 74-year-old woman was found on routine transthoracic echocardiography to have a linear echogenic structure that was initially concerning for a dissection flap. A computed tomography angiogram of the aorta revealed a linear density that followed the curvature of the aortic arch, which was concerning for a retained angioplasty wire from a percutaneous coronary intervention done 11 years earlier. Because the patient had not reported any symptoms, a multidisciplinary decision was made to defer any surgical intervention.